Mastication of crisp bread: Role of bread texture and structure on texture perception - Aleixandre, Andrea; Benavent-Gil, Yaiza; Velickova, Elena and Rosell, Cristina M. (elsevier, 2021)
Texture and structure of breads have been related to oral processing (FOP) performance and sensory perceptions, but moisture content might play a significant role. To evaluate the real impact of breads texture and structure, eliminating the possible role of moisture content, different toasted breads were investigated. Four commercial toasted sliced breads (white bread -WHB-, whole wheat bread -WWB-, non-added sugar bread -NSU-, non-added salt bread -NSA-) with similar ingredients but different texture and structure were selected. Texture and structure were instrumentally and sensory evaluated, besides FOP (total chewing time, number of chews until swallowing, chewing frequency, and mouthful) and bolus properties (moisture, saliva to bread ratio, hardness, adhesiveness, and cohesiveness). Toasted breads showed significant differences in hardness, cutting strength, and porosity, but panelists did not discriminate among them. FOP results indicated that harder samples (NSU) required longer mastication and a number of chews, and open crumb structures (WWB, WHB) with higher cell areas required less mastication. Also, bolus characteristics were affected by bread types, and bread with lower crumb hardness (WHB) produced more cohesive bolus. Having toasted breads allowed to eliminate possible influence of moisture content differences on sensory perception, mouthful and bolus water incorporation during mastication.
Keywords: Bread Texture Sensory perception FOP Mastication Bolus properties